The book and the roses: Sufi women, visibility and Zikir in contemporary Istanbul - Raudvere, Catharina (Transactions / Swedish Research Institute in Istanbul, 2002)
Encountering Sufism in contemporary Istanbul -- Access, visibility, and mobility. Islam in Turkey after 1983 -- Gönenli's group : Sufi women constructing rooms of their own -- Get exuberant with zikir : women in command of commemorative prayers -- Political Sufism and spiritual Islamism